Differences in extent of mechano-induced QT-changes in SQTS, WT and LQTS rabbit models. (14th October 2021) - Nimani, S; Hornyik, T; Alerni, N; Lewetag, R; Giammarino, L; Perez-Feliz, S; Matas, L; Moss, K R; Zehender, M; Brunner, M; Seemann, G; Odening, K E
Abstract: Background: Electro-mechanical (EMC) and mechano-electrical coupling (MEC) are essential for normal cardiac function. Alterations in these can result in increased arrhythmia formation. In "electrical" cardiac diseases, long-QT and short-QT syndrome, regional mechanical function is altered via EMC. Purpose: In this study, we aimed to investigate how acute changes in mechanics may impact on electrical function (MEC) in these diseases. Methods: To determine how acute changes in preload impact on QT duration, adult rabbits of both sexes were given a 6ml/kg BW bolus of 0.9% NaCl IV and 12-lead-ECGs were assessed first in wildtype (WT) and acquired drug-induced (E4031 to block IKr) LQT2 ("aLQT2") rabbits, and in a second step in transgenic short-QT type 1 ("SQT1", KCNH2-N588K) and WT littermate control rabbits ("WT-LMC"). Results: At baseline, aLQT2 rabbits demonstrated a markedly prolonged heart-rate corrected QTc duration compared to WT (p<0.0001; n=13), with increased QT-dispersion (QTMax-Min [ms], WT 21.4±5.7 vs. aLQT2 25.8±5.8; p=0.003; n=13) and increased short-term variability of QT (STVQT [ms], WT 3.5±1.0 vs. aLQT2 5.3±1.7; p=0.02; n=13), markers for regional and temporal heterogeneity of repolarization, respectively. SQT1 rabbits (n=8) demonstrated a shorter QTc duration compared to WT-LMC (n=10; p=0.04), with no differences in QT-dispersion and STVQT between the two groups. Increased preload acutely prolonged QT and heart-rate corrected QTc in all groups (despite a slight increase in heart-rate by an average of 25 beats/min): in WT [ms] 171.6±11.6 to 213.3±20.3 (p<0.0001) vs. aLQT2 208.9±19.6 to 271.0±37.5 (p<0.0001; n=13 each), and in WT-LMC 171.3±4.8 to 199.2±5.4 (p<0.0001; n=10) vs. SQT1 156.0±4.7 to 177.3±3.5 (p=0.0004; n=8). Importantly, the extent of mechano-induced electrical changes differed among genotypes, with less pronounced QTc prolongation in SQT1 compared to WT-LMC (delta QTc [ms], SQT1 21.2±3.4 (n=8) vs. WT-LMC 27.9±2.8 (n=10; p=0.15)), and a more pronounced QTc prolongation in aLQT2 compared to WT (delta QTc [ms], WT 41.6±14.9 vs. aLQT2 62.1±32.1; p=0.006; n=13 each). Moreover, QT-dispersion was increased significantly upon global mechanical change only in aLQTS (QTMax-Min [ms], 25.8±5.5 to 32.7±12.3; p=0.03; n=13). Conclusion: Acute changes in mechanical function result in electrical changes via MEC in SQT1, WT and aLQT2 rabbits. The extent of these changes, however, depends on the underlying QTc duration, with the least pronounced QTc prolongation in SQT1 rabbits, with the shortest QTc, and the most pronounced QTc prolongation in aLQT2 rabbits, with the longest QTc. The most pronounced MEC effects on global QT duration as well as on regional QT dispersion in aLQT2 indicate that acute MEC effects may play an additional role in LQTS-related arrhythmogenesis. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): German Research Foundation (DFG) andSwiss National Science Foundation (SNF)